Q&A - Ask Doubts and Get Answers
Q

Simplify and express the result in power notation with positive exponent. (v) 2^ -3 x - 7 ^ -3

Q2. Simplify and express the result in power notation with positive exponent.

    (v) 2^{-3} \times (-7)^{-3}

Answers (1)
Views
M manish

The detailed solution for the above-written question is as follows,

we know the exponential forms

a^{-m}=\frac{1}{a^{m}}         &         a^{m}\times b^{m}= (ab)^{m}

So, according to our data,

here initially we use first forms and then the second one.

2^{-3}\times (-7)^{-3}= \frac{1}{2^{3}}\times \frac{1}{(-7)^{3}}

                             = \frac{1}{(2\times -7)^{3}}= \frac{1}{(-14)^{3}}

Exams
Articles
Questions